Metoprolol retard effectiveness in patients with arterial hypertension and disturbed circadian blood pressure rhythm - P. P. Tikhonov; L. A. Sokolova (Кардиоваскулярная терапия и профилактика)
Aim. To study metoprolol retard antihypertensive effects and its influence on circadian blood pressure (BP) profile, according to BP circadian rhythm type. Material and methods. The study included 20 patients with Stage I-II essential arterial hypertension (EAH). At baseline and after one-month metoprolol retard therapy (100 mg/d), 24-hour BP monitoring (BPM) was performed. According to BPM results, all patients were divided into two groups: Group D («dippers»), and Group ND («non-dippers»). Both groups were comparable by mean age, EAH duration, and BP levels. Results. By the end of the study, BP normalized in 45% (n=5) of Group D participants, and in 78% (n=7) of Group ND subjects. In both groups, mean 24-hour BP, daytime and nighttime BP, BP load, and BP variability decreased. BP decrease in Group ND was significantly greater than in Group D. The difference was statistically significant for mean 24-hour BP, daytime and nighttime systolic BP. Metoprolol retard did not affect circadian index (CI) and proportion of different circadian rhythm types. Nevertheless, during the therapy, «night-peakers» (CI<0) and «over-dippers» (CI>20%) were absent, «non-dippers» were rare, and, as a result, «dippers» number increased. Metoprolol retard (100 mg/d) tolerability was satisfactory in both groups. Аdverse effects – sleepiness, headache, nose stuffiness – did not result in medication withdrawal. Conclusion. Metoprolol had especially high antihypertensive effectiveness in patients with inadequate nighttime BP decrease.